2009
DOI: 10.1111/j.1468-2958.2009.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents Don’t (Always) Know Their Children Have Been Bullied: Child-Parent Discrepancy on Bullying and Family-Level Profile of Communication Standards

Abstract: Discrepancy between bullied victims' experience and their parents' understanding indicates underutilization of family support system, and thus presents an important risk factor. An online survey (N = 300 child-father-mother triads) was conducted to establish a framework that helps distinguish families with different child-parent discrepancy levels. This family-level variability was modeled by profiling child-father-mother triad's family communication standard (FCS) orientations. This ''FCS profile'' indeed dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 61 publications
2
47
0
5
Order By: Relevance
“…In fact, recent findings suggest that relational and interactional factors make significant differences in individuals' management of difficult information, in general, and bullied victims' disclosure and coping, in particular. For example, Matsunaga (2009) found that communicative dispositions of family were related to parents' understanding of bullying; parents of the families with an open and affectionate orientation knew more accurately than others about whether their children were bullied and how severely they were victimized. Afifi and Steuber (2009) have demonstrated that individuals assess the risk of revealing secret information to someone vis-à-vis their relationship with that person and this risk assessment, in turn, predicts the actual communication strategy used by those individuals in revealing the secret.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…In fact, recent findings suggest that relational and interactional factors make significant differences in individuals' management of difficult information, in general, and bullied victims' disclosure and coping, in particular. For example, Matsunaga (2009) found that communicative dispositions of family were related to parents' understanding of bullying; parents of the families with an open and affectionate orientation knew more accurately than others about whether their children were bullied and how severely they were victimized. Afifi and Steuber (2009) have demonstrated that individuals assess the risk of revealing secret information to someone vis-à-vis their relationship with that person and this risk assessment, in turn, predicts the actual communication strategy used by those individuals in revealing the secret.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…For example, child disclosure is stimulated in the context of high parental responsiveness, high behavioral control, and low psychological control (Soenens et al 2006). Specifically in relation to the victimization of bullying, parental knowledge about this is most likely in an open and affectionate family climate (Matsunaga 2009). …”
Section: Parental Knowledge Of Children's Offline Behaviormentioning
confidence: 99%
“…Studies show that parents are often unaware of their children's internet behavior and experiences. For example, among younger as well as older adolescents, studies found that parents tend to underestimate their children's own cyberbullying behavior as well as their children's experiences with cyberbully victimization (Byrne, Katz, Lee, Linz, & McIlrath, 2014;Dehue, Bolman, & Völlink, 2008;Matsunaga, 2009). An in-depth study on parental mediation among younger children found that parents tend to be confident in their internet parenting, but the author suggests that this confidence is not always substantiated and may be biased due to the low actual parental involvement in children's internet use (Shin, 2015).…”
Section: Performing Parental Mediationmentioning
confidence: 99%